Consumer taste uncertainty in the context of store brand and national brand competition - Arcan Nalca; Tamer Boyaci; Saibal Ray (European School of Management and Technology (ESMT), 2017)
In this paper, we focus on the uncertainty in consumer taste and study how a retailer can benefit from acquiring that taste information in the presence of competition between the retailer's store brand and a manufacturer's national brand. In this context, we also identify the optimal information sharing strategy of the retailer with the manufacturer as well as the equilibrium product positioning and pricing of the two brands. We model a competitive setting in which there is ex-ante uncertainty about consumer preferences for different product features and the retailer has a distinct advantage in terms of resolving this uncertainty, given his close proximity to the consumers. We identify two important effects of retailer's information acquisition and sharing decisions about consumer taste. The direct effect is that having taste information allows the retailer to make better SB introduction and positioning decisions. The indirect effect is that information sharing enables the manufacturer to make better NB positioning decisions - which in return may benefit or hurt the retailer. Furthermore, we show that these effects interact with each other and the nature of their interaction depends on three external factors: relative popularity of different product features, the vertical differentiation between the two brands, and the cost of store brand introduction. This interaction is most striking when the store brand introduction is not very costly. In this case, if one of the features is quite popular, then the retailer voluntarily shares information with the manufacturer because the indirect effect augments the value of the direct effect - even though this increases the competition between the brands. Otherwise, the retailer refrains from information sharing because the indirect effect then diminishes the value of the direct effect. We also generate managerial insights as to when it is most valuable for the retailer to acquire taste information as well its worth for the manufacturer.
urn:nbn:de:101:1-201702134107; More recent version: http://hdl.handle.net/10419/173244
Keywords: 650; uncertain consumer taste; product introduction; store brands; national brands; information acquisition; information sharing; vertical differentiation; horizontal differentiation